Relationship between macro nutrient intake, physical activity, and stress levels in police officers - Handayani, Winahyu; Ratnayani; Avicena, Rasyid (Bulan Sabit Merah Indonesia, 2025)
Overweight cases in Banten from 2022 obesity cases increased by 22%. According to data from the Medical and Police Department (SIDOKKES) of the Cilegon City Police, the prevalence of overweight cases was 19.2% of male police officers experiencing overweight status. This study is a quantitative and observational study with a cross-sectional research design. This study aims to determine the relationship between nutrient intake, physical activity and stress levels with the incidence of obesity in police officers at the Cilegon City Police. The sample in this study were police officers at the Cilegon City Police. The results of the study concluded that the nutritional status of police officers was 60.8% experiencing normal nutrition and 39.2% experiencing overweight, with an average energy intake of 2497 Cal, 79.35 grams of protein, 87.3 grams of fat, and 350.6 grams of carbohydrates. Overall, most respondents had adequate energy, fat, and carbohydrates in the normal category. While the level of energy sufficiency in the category above the requirement figure, Judging from physical activity as many as 20.3% have light physical activity, 65.8% have moderate physical activity, and 13.9% have heavy physical activity, Based on stress levels as many as 77.2% experience light stress and 22.8% experience moderate stress, 22.8% experience moderate stress. 5. There is no significant relationship between energy intake (P = 0.333) and protein (P = 0.168) with nutritional status, but there is a significant relationship between fat intake (P = 0.030) and carbohydrates (P = 0.006) with nutritional status, There is a significant relationship between physical activity and nutritional status (P = 0.000), There is no significant relationship between stress levels and nutritional status (P = 0.607).